Awareness and acceptance of labour analgesia in rural india - Shrikrishna Govindrao Deogaonkar; Suhit Natekar (International Journal of Medical Research and Review, 2016)
Study has been carried out at Pravara Rural Hospital regarding awareness among expecting mothers about Labour Analgesia. Parturients attending ANC clinic were interviewed by anaesthesia residents according to questionaire prepared and responses were recorded. We wanted to study knowledge about labour analgesia in rural parts of India.Method: After getting permission from ethical committee, 250 pregnant women attending ANC clinic were interviewed by anaesthesia residents according to prepared questionnaire and responses recorded. Parturients not willing to participate were excluded from study.Results: Maximum (78%) respondents were from rural area. Their educational level was poor (39% were illiterate and 36% could only read and write). Majority of parturients belonged to low socio-economic group (76%). Awareness about painless delivery was minimal (98%), and after giving information about labour analgesia most (90%) were willing to experience painless delivery.Discussion: As pain during delivery is most excruciating and can have impact on future of expecting mothers, nowadays methods to relieve pain of delivery are available. Still labour analgesia is not known to expecting mothers and not commonly used in rural India. Same is the condition in developing countries as shown by various studies.Conclusion: Various methods need to be adopted to make expecting mothers aware about labour analgesia. Similarly, practicing obstetricians should encourage parturients for pain free delivery.